2017
DOI: 10.9734/arja/2017/38290
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risks of Several Insecticides towards Honeybee Workers

Abstract: The risk level of several insecticides of various chemical classes was estimated for honeybee workers, Apis mellifera L. (Hymenoptera: Apidae). Lethal time calculation was used to risk assessment for honeybees. Bioassay tests were conducted with six insecticides [dinotefuran (neonicotinoid), methomyl (carbamate), profenofos (organophosphate), azadirachtin (botanicalbioinsecticide), spinosad (bioinsecticide-an extract of the fermentation broth of soil actinomycete) and chlorfluazuron (IGR)] on honeybee workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The later one is a neonicotinoid insecticide never approved to be marketed in the European Union and currently under reevaluation in the USA, because of the high risk offered to bees and other pollinators. Azab and Morsy (2017) demonstrated that in higher concentrations (1Fx10 -1 and 5Fx10 -2 , F = recommended field rate in ug active ingredient mL -1 ), dinotefuran caused 100% of bee mortality after one day of exposure. Corroborating these data, Yasuda et al (2017) shown that among the neonicotinoid's insecticides acetamiprid, imidacloprid, clothianidin, thiamethoxam, and dinotefuran, the latter was the most toxic for bees (LD50, 1.4 ng/bee).…”
Section: Brazilian Legislation and Its Relation With The Increased Release Of Pesticides And Bee Mortalitymentioning
confidence: 99%
“…The later one is a neonicotinoid insecticide never approved to be marketed in the European Union and currently under reevaluation in the USA, because of the high risk offered to bees and other pollinators. Azab and Morsy (2017) demonstrated that in higher concentrations (1Fx10 -1 and 5Fx10 -2 , F = recommended field rate in ug active ingredient mL -1 ), dinotefuran caused 100% of bee mortality after one day of exposure. Corroborating these data, Yasuda et al (2017) shown that among the neonicotinoid's insecticides acetamiprid, imidacloprid, clothianidin, thiamethoxam, and dinotefuran, the latter was the most toxic for bees (LD50, 1.4 ng/bee).…”
Section: Brazilian Legislation and Its Relation With The Increased Release Of Pesticides And Bee Mortalitymentioning
confidence: 99%